Spices : A survey of the world market - International Trade Centre (ITC) (Geneva : ITC Publications, 1982)
Volume 2 of this publication covers 22 significant market countries in North and Latin America, Asia, Oceania, Middle East and North Africa; country chapters typically review supply situation, market characteristics, distribution network, trade practices, promotion and market access factors and give useful addresses.
ne 4/04/2018
Loan
Keywords: Market survey